Pattern Recognition and Information Processing c - Ablameyko, Sergey V.; Krasnoproshin, Viktor V.; Lukashevich, Maryna M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book constitutes the refereed proceedings of the 14th International Conference on Pattern Recognition and Information Processing, PRIP 2019, held in Minsk, Belarus, in May 2019. The 25 revised full papers were carefully reviewed and selected from 120 submissions. The papers of this volume are organized in topical sections on pattern recognition and image analysis; information processing and applications.
Keywords: Pattern recognition; Optical data processing; Artificial intelligence; Computers; Architecture, Computer; Pattern Recognition; Image Processing and Computer Vision; Artificial Intelligence; Information Systems and Communication Service; Computer System Implementation